Economic incentives for the wildlife trade and costs of epidemics compared across individual, national, and global scales. Issue 7 (6th June 2022) - de Wit, Luz A.; Fisher, Brendan; Naidoo, Robin; Ricketts, Taylor H.
Abstract: The wildlife trade drives biodiversity loss and zoonotic disease emergence, and the health and economic impacts of COVID‐19 have sparked discussions over stricter regulation of the wildlife trade. Yet regulation for conservation and health purposes is at odds with the economic incentives provided by this multibillion‐dollar industry. To understand why the wildlife trade persists despite associated biodiversity and global health threats, we used a benefit–cost approach using simple calculations to compare the economic benefits of the wildlife trade at the individual, national, and global scales to the costs of COVID‐19, severe acute respiratory syndrome (SARS), and Ebola disease across scenarios of epidemic frequency. For COVID‐19, benefits of the wildlife trade outweigh costs at individual scales, but costs far exceed benefits at national and global scales, particularly if epidemics were to become frequent. For SARS and Ebola, benefits outweigh costs at all scales, except if Ebola‐like epidemics were to become frequent. The wildlife trade produces net benefits for people who depend on wildlife for food and income but incurs net costs on stakeholders at larger scales from increased epidemic risk. While our analysis omits a variety of costs and benefits that are difficult to quantify and contrast, our analysis is meant to illustrate the distributional outcomes across stakeholder groups that could result from increased wildlife trade regulation. Importantly, the feasibility of trade regulatory policies will depend on how these benefits and costs compare across groups and would therefore need to involve accessible and attractive alternative sources of food and livelihoods for those who depend on the wildlife trade.